Exploring high temperature templating in non-planar phthalocyanine/copper iodide (111) bilayers. Issue 2 (25th November 2014) - Ramadan, Alexandra J.; Rochford, Luke A.; Keeble, Dean S.; Sullivan, Paul; Ryan, Mary P.; Jones, Tim S.; Heutz, Sandrine
Abstract : Controlling the structure of organic small molecule thin films is of considerable interest for organic electronic devices. Concurrent use of a copper iodide templating layer with deposition onto heated substrates allows previously unreported morphologies and molecular orientations of vanadyl phthalocyanine to be produced. Abstract : Elevated substrate temperature growth of phthalocyanine thin films is known to influence film morphology and increase crystallinity. Structural templating offers another method through which the structure of phthalocyanine films can be controlled. Here we combine the use of copper iodide (CuI) and elevated substrate temperatures and investigate their effect on the growth of a non-planar phthalocyanine system. Employing X-ray diffraction and atomic force microscopy we present detailed surface and crystal structure information. Vanadyl phthalocyanine (VOPc) is shown to adopt an edge-on orientation on CuI at ambient substrate temperatures, a behaviour in stark contrast to that of previously studied planar phthalocyanine molecules. Elevated substrate temperature is shown to result in changes in the surface morphology and structure demonstrating the versatility of the system. The crystal structure of VOPc was redetermined and used to infer the molecular orientation of the various VOPc/CuI bilayer structures.